Preliminary Investigation on the Useful Chemicals obtained from High-Temperature and High-Pressure Water Treatment of Hinoki (Chamaecyparis Obutus) Bark - Daimon, Hiroyuki; Faisal, Muhammad (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2010)
The possibility of utilizing residual forest biomass to produce valuable chemicals was investigated. An outer layer of a bark of Hinoki (Chamaecyparis obutusa) tree, a Japanese cypress, was used as a sample material. Experiments were carried out in a semibatch reactor apparatus that allows the study of the effect of reaction temperatures in a single run. Analysis of the products by GC-MS reveals formation of useful compounds such as furfural, some aromatic compounds (1,3-di-tert-butyl benzene and 2,4-di-tert-butyl phenol), and fatty acids (myristic acid, palmitic acid and stearic acid).Keywords: fatty acids, furfural, high temperature water treatment, hinoki, residual biomass